Effects of Different Recovery Positions on the Postpercutaneous Liver Biopsy Complications: A Metaanalysis - Zhong, Chengli; Jin, Jiandi; Wang, Xiaoyan; Huang, Yandi; Yan, Dong; Wang, Wei (Frontiers in Surgery, 2021)
Objective: We aim to evaluate the effects of different recovery position on the adverse events and the patient acceptability in those underwent percutaneous liver biopsy (PLB). Methods: Literature search was given to the articles in Cochrane Library, Embase, Scopus, PubMed, CNKI, Sinomed, and Wanfang databases. The time for the article extraction was until July 2020. The articles were screened by two independent researchers, together with the bias risk evaluation and data extraction. The RevMan 5.4 software was utilized for the Meta-analysis. Results: Finally, two articles involving 180 subjects were eligible in this study. Meta-analysis showed that at T0, the alternation between right-side and combined position (CRP) would induce elevation of post-PLB pain compared with the dorsal/supine position (SRP) [WMD=-2.00, 95% CI (-3.54, -0.47), p=0.01]. There were no statistical differences in the postoperative pain among the CRP, SRP and right-side position (RRP). The patient acceptability of SRP and RRP was higher than that of the CRP. Finally, two eligible studies were included, which showed no incidence of pneumothorax and abdominal bleeding. Conclusions: CRP would induce post-PLB pain at T0. SRP was the most acceptable position for the cases underwent PLB. There were no statistical differences in the incidence of pneumothorax and abdominal bleeding.